Market research and overview of Turkish hygienic products - (:unkn) unknown (WOODHEAD PUBL LTD, 2006)
In this research all the hygiene products currently sold in the Turkish market have been investigated. All exports and imports with countries of origin and volumes have been studied. Market capacity is also researched and the results are discussed.